PATHOMORPHOSIS OF DISEASES OF THE DIGESTIVE SYSTEM ALLERGIC AND NON ALLERGIC GENESIS IN CHILDREN OF UKRAINE IN THE DYNAMICS OF 25 YEARS OF OBSERVATION - Volosovets О.P.; Кryuchko T.O.; Marushko, Yu.V.; Shadrin O.Н.; Volosovets, T.M.; Pochynok, T.V.; Churylina, A.V. (World of Medicine and Biology, 2022)
The purpose of the study was a retrospective 25 year analysis of the incidence and prevalence of the digestive system diseases of allergic and non-allergic genesis in children of Ukraine to determine the possibility of environmental factors’ influence on their development. We have used methods of system approach, epidemiological, correlation and cluster analysis of medical statistics data of the Ministry of Health of Ukraine. A retrospective study from 1993 to 2017 have revealed that among children of Ukraine (aged 0–17 years included) there was a tendency of increasing the prevalence of diseases of the digestive system by 13.6 %, as well as their incidence – by 12.1 %, еspecially it is related to the children, affected by the Chernobyl accident. Over 25 years there have been significant changes in their structure, which requires careful attention to the above contingent of children.